RETRACTED: Neural Correlates of Handwriting Effects in L2 Learners - Li, Yifei; Guan, Connie Qun (Frontiers in Psychology, 2022)
Learning to write involves integrating motor production and visual perception to develop orthographic representations. This study tries to test the effect of hand movement training as a pathway to neural correlates for L2 Chinese and L2 English readers. Twenty L2 Chinese and 20 L2 English (n = 20) adults participated in both behavioral and electroencephalogram (EEG) experiments. We designed six learning conditions: Hand Writing Chinese (HC), Viewing Chinese (VC), Drawing followed by Character Recognition in Chinese (DC), Hand Writing English (HE), Viewing English (VE), and Drawing followed by Word Recognition in English (DE). Behavioral and EEG results demonstrated that drawing facilitated visual word recognition in Chinese compared to viewing. The findings imply that hand movement could strengthen the neural processing and improve behavioral performance in Chinese character recognition for L2 Chinese learners and English word recognition for L2 Chinese learners. Furthermore, N170 amplitude at the drawing condition was positively correlated with N400 amplitudes. Thus, the early visual word recognition neural indicator (e.g., N170) was predictive of the late neural indicator of semantic processing (e.g., N400), suggesting that hand movement facilitates the neural correlates between early word recognition and later comprehension.